Transcutaneous Electrical Nerve Stimulation in the pain of cancer patients in palliative care: an integrative review (Research, Society and Development, 2022)
To present the effects and protocols of Transcutaneous Electrical Nerve Stimulation (TENS) on cancer pain in patients undergoing palliative care. This is an integrative literature review, with a bibliographic survey carried out in May and June 2022. The sample for this review consisted of four studies, one of which was found on Scopus database, two on PubMed and one on Embase. The included studies presented TENS as a physiotherapeutic resource for pain relief, safe, non-invasive and low cost, which had few adverse effects and enabled a reduction in the use of analgesic medications. There was variation in their application protocols and therapy time. The scarcity of studies found on the subject is highlighted, a scenario that reflects the need for research that focuses on pain relief, care and attention to cancer patients in palliative care.